Zmiana zachowań rynkowych pokolenia Z - Paczka, Edyta (Wydawnictwo Uniwersytetu Wrocławskiego, 2020)
This article presents considerations on the changes of the consumer behaviour of generation Z, manifested in the way purchasing decisions are made and needs are met. The purpose of this article is to analyse the conditions for the development of new forms of purchasing processes and alternative consumption patterns. The author pointed out factors causing young purchasers’ increased interest in innovative solutions in the sphere of consumption, and, in particular, the expanding scope of internet communication and the scale of use of mobile devices. It has been proved that the generation Z consumption model is strongly embedded in virtual reality and includes an alternative approach to satisfying needs. An attempt was made to answer the question regarding the reason for a change in approach of the youngest generation to consumption and the development of new trends, and in particular of the resignation from purchasing goods in favour of gaining access to them. The author indicated certain premises increasing generation Z’s inclination to use some goods or servicesonly when required, and not acquiring them for personal possession, including, in particular, growing awareness of the negative social and environmental consequences of excessive consumption. Benefits of adapting the collaborative consumption model in the form of prosumer activities were highlighted. The presented topic allowed to show the changing approach to consumptionas a challenge for enterprises facing the need to react both to the changing mobile technological environment and to the new, emerging generation of consumers. So far, this problem has not been studied in detail, therefore the conclusions of the article on changing consumer attitudes of generation Z may be used by manufacturers to take actions consistent with the expectations of this significant group of young, mobile buyers.
Keywords: generation Z; changes in consumer behaviour; innovations in consumption; collaborative consumption; prosumption